2018
DOI: 10.1371/journal.pone.0206076
|View full text |Cite
|
Sign up to set email alerts
|

The Why We Retweet scale

Abstract: BackgroundTwitter offers a platform for rapid diffusion of information and its users' attitudes and behaviors. Insights about information propagation via retweets (the message forwarding function) offer observable explanations of ways in which modern human interactions get organized in the form of online networks, and contextualized in the form of public health, policy decisions, disaster management, and civic participation. This study conceptualized and validated the Why We Retweet Scale to contextualize retw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 26 publications
2
23
0
2
Order By: Relevance
“…A common refrain on Twitter is that "likes and/or retweets do not equal endorsements," and the same can be said here. Though we find that simpler language corresponds with more social engagements, we cannot say whether these behaviors indicate more liking or support for the content in question given that people commonly engage with content they dislike or disagree with as well (40,41). Although we acknowledge our inability to address the motivation for engagement directly, the size and diversity of our samples suggests the presence of differential motivations for engagement are likely distributed evenly across the same sample.…”
Section: Discussionmentioning
confidence: 70%
“…A common refrain on Twitter is that "likes and/or retweets do not equal endorsements," and the same can be said here. Though we find that simpler language corresponds with more social engagements, we cannot say whether these behaviors indicate more liking or support for the content in question given that people commonly engage with content they dislike or disagree with as well (40,41). Although we acknowledge our inability to address the motivation for engagement directly, the size and diversity of our samples suggests the presence of differential motivations for engagement are likely distributed evenly across the same sample.…”
Section: Discussionmentioning
confidence: 70%
“…Prior work has shown that a retweet demonstrates support for the author of the original tweet, but the significance of a retweeted message remains unclear. 23 Future studies are needed to examine how support interventions that use social media can be designed effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Due to this asymmetry, users can re-create and reinforce traditional hierarchical network structures in Twitter by relying on just a few information sources or by choosing to limit interactions to a select group of similar others (Himelboim et al, 2017). Thus, the connections built among users are indicators of information sharing and network structures reflect patterns of information flow (Himelboim et al, 2017;Majmundar et al, 2018).…”
mentioning
confidence: 99%